Description of The Quality of Etawa Breeding Goat Meat At Room Temperature Viewed From Color and Smell Raised in Bali - Alif Ilham Ilahi (Institute for Research and Community Service, Udayana University, 2023)
The offsring of etawa goat (PE) is one of the local goat breeds that are often found in Indonesia, including in Bali island. Assessment of the quality of PE goat meat is one of the things that needs to be considered because it is often equated with other types of livestock meat, this occurs due to the lack of publications regarding the assessment of the quality of goat meat, especially PE goat meat. Color and smell are aspects of the assessment of a meat quality. The aim of this study was to investigate the quality of PE goat meat at room temperature in terms of color and smell within 24 hours. Samples were taken from goat farms in Desa Serpang, Kecamatan Busungbiu Kabupaten Buleleng, Provinsi Bali. The goat samples taken were meat from goats shortly after slaughtered. Tests carried out on PE goat meat were color and odor tests, color tests were carried out using SNI color standards, while odor tests were tested by panelists. This study used a descriptive-quantitative model with ANOVA test and continued with Duncan's test. Keywords: PE Goat, Color, Smell, Time